PRODUCT DIVERSIFICATION: MARKETING MANAGEMENT STRATEGY FOR BUSINESS GROWTH - Ismail Razak (SEAN Institute, 2022)
In an era of globalization and increasingly fierce competition, companies are required to continue to innovate and adapt their product portfolio to changing market needs. Product diversification has been recognized as one of the main approaches to achieving sustainable business growth. This research aims to investigate the role of product diversification strategies in increasing business growth through implementing effective marketing management. This research uses a qualitative approach with descriptive methods. The research results show that product diversification is effective as a marketing management strategy for business growth. By diversifying the product portfolio, companies can be more responsive to changing market needs, increase competitiveness, and manage risk by mitigating negative impacts on business performance. Innovation and creativity in product development are the keys to creating added value and overcoming competition. In addition, effective marketing of product diversity can increase consumer awareness, expand market share, and build a strong brand image. The research results confirm that product diversification is not only an adaptation measure, but also a proactive strategy that supports sustainable growth and sustainability of the company's business.